Protective effect of Phellinus linteus polysaccharide extracts against thioacetamide-induced liver fibrosis in rats: a proteomics analysis - Wang Hualin; Wu Guang; Park Hyoung Jin; Jiang Ping Ping; Sit Wai-Hung; van Griensven Leo JLD; Wan Jennifer Man-Fan (BMC, 2012)
Abstract Background The hepatoprotective potential of Phellinus linteus polysaccharide (PLP) extracts has been described. However, the molecular mechanism of PLP for the inhibition of liver fibrosis is unclear. This study aims to investigate the molecular protein signatures involved in the hepatoprotective mechanisms of PLP via a proteomics approach using a thioacetamide (TAA)-induced liver fibrosis rat model. Methods Male Sprague-Dawley rats were divided into three groups of six as follows: Normal group; TAA group, in which rats received TAA only; and PLP group, in which rats received PLP and TAA. Liver fibrosis was induced in the rats by repeated intraperitoneal injections of TAA at a dose of 200 mg/kg body weight twice a week for 4 weeks. PLP was given orally at a dose of 50 mg/kg body weight twice a day from the beginning of the TAA treatment until the end of the experiment. The development of liver cirrhosis was verified by histological examination. Liver proteomes were established by two-dimensional gel electrophoresis. Proteins with significantly altered expression levels were identified by matrix-assisted laser desorption/ionization-time of flight/time of flight mass spectrometry and the differentially expressed proteins were validated by immunohistochemical staining and reverse transcription polymerase chain reaction. Results Histological staining showed a remarkable reduction in liver fibrosis in the rats with PLP treatment. A total of 13 differentially expressed proteins including actin, tubulin alpha-1C chain, preprohaptoglobin, hemopexin, galectin-5, glutathione S-transferase alpha-4 (GSTA4), branched chain keto acid dehydrogenase hterotetrameric E1 subunit alpha (BCKDHA), glutathione S-transferase mu (GSTmu); glyceraldehyde-3-phosphate dehydrogenase (GAPDH); thiosulfate sulfurtransferase (TFT); betaine-homocysteine S-methyltransferase 1 (BHMT1); quinoid dihydropteridine reductase (QDPR); ribonuclease UK114 were observed between the TAA and PLP groups. These proteins are involved in oxidative stress, heme and iron metabolism, cysteine metabolism, and branched-chain amino acid catabolism. Conclusion The proteomics data indicate that P. linteus may be protective against TAA-induced liver fibrosis via regulation of oxidative stress pathways, heat shock pathways, and metabolic pathways for amino acids and nucleic acids.